Low-grade heat and its definitions of Coefficient-of-Performance (COP). (5th June 2015) - Wang, Lin-Shu; Ma, Peizheng
Abstract: Use of fire for low grade heat, still widely practiced today, is wasteful because it is based on the principle of heat production – which should have become an outmoded idea post-Carnot for low grade heat application as an exergy analysis will readily conclude. Instead of application of exergy analysis, a new thermodynamic analysis resulting from the unification of Kelvin's energy principle and the entropy principle, formulated recently (called the entropic theory of heat), is applied here to reexamine the problem of building heating. Other than improving envelope heat resistance, conventional building efficiency gain is predominantly obtained by improving HVAC efficiency (i.e., boiler efficiency); our finding shows that there is in fact large room in improving the building heating operation surpassing 100% boiler efficiency, as demonstrated by the large value of the Kelvin limit (the theoretical upper bound of Thermal COP). This theoretical possibility of generous amount of heat from fire suggests additional possibilities of heat from primary energy other than fire, and the disclosure of these possibilities by applying the triad framework in the entropic theory of heat in terms of alternative definitions of Coefficient of Performance (COP). Consideration of such alternative COPs suggests real possibility of efficiently and cost effectively obtaining low grade heat from primary energy. Highlights: Importance of thinking heat extraction for high energy efficiency in buildings. The concept of Thermal COP and the determination of its (maximum) Kelvin limit. Key to find the sweet spot of using heat pump is thinking general heat extraction. triadCOP & eThermalCOP are measure of energy transformation in the triad framework.